2022
DOI: 10.47841/jsoshum.v3i2.157
|View full text |Cite
|
Sign up to set email alerts
|

Program Pelatihan Digitalisasi Media Literasi  Untuk Pendidikan Bahasa dan Sastra di Kota Tegal Jawa Tengah

Abstract: Kegiatan literasi masyarakat Kota Tegal tengah mengalami perkembangan yang cukup signifikan dimana pemerintah Kota Tegal memberikan perhatian kepada masyarakat dengan memberikan fasilitas dan program-program unggulan literasi. Masyarakat juga cukup produktif dalam menghasilkan karya sastra serta teks-teks yang dapat digunakan untuk pembelajaran bahasa. Di sisi lain, kemajuan teknologi digital belum banyak dimanfaatkan untuk pengembangan potensi masyarakat ini. Dengan adanya potensi-potensi sumber daya tersebut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The use of Spotify as a platform for listening to fairy tales brings two main elements, namely reading in the traditional sense, where children consume the story by listening to the narrative, and listening, where they interact with the sounds, music, and sound effects used in the fairy tale. Furthermore, research by (Meiristiani et al, 2022) shows that increasing public literacy is driven by government support and productivity in creating literary works. However, the use of digital technology still needs to be improved.…”
Section: Trends In the Development Of Audiobooks Past And Presentmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of Spotify as a platform for listening to fairy tales brings two main elements, namely reading in the traditional sense, where children consume the story by listening to the narrative, and listening, where they interact with the sounds, music, and sound effects used in the fairy tale. Furthermore, research by (Meiristiani et al, 2022) shows that increasing public literacy is driven by government support and productivity in creating literary works. However, the use of digital technology still needs to be improved.…”
Section: Trends In the Development Of Audiobooks Past And Presentmentioning
confidence: 99%
“…In Indonesia, audiobooks are often used in education as alternative learning media. A study by (Meiristiani et al, 2022) found that the transformation of literary works and texts from the community were transformed from text to audio formats, such as audiobooks and podcasts, to develop digital literacy media for language and literature education for the community. (Pratiwi et al, 2022) said that the implications of audiobooks affect students' ability to become more fluent in reading.…”
Section: Trends In the Development Of Audiobooks Past And Presentmentioning
confidence: 99%
“…Thus, the Audiobook Media of Madurese folklore is a concrete form that can maintain and preserve Madurese folklore. It is stated by Meiristiani et al that in Malaysia, audiobooks are also used as an alternative to reading Malay literary works to provide a new experience to the listener [18]. In other words, the audiobook publication aims to preserve or promote local literary works through digital technology.…”
Section: Audiobooks As a Means Of Preserving Madurese Folklorementioning
confidence: 99%